Pendaftaran Tanah Sistematis Lengkap (PTSL) Terhadap Tanah Registrasi Desa (Letter C) di Desa Mangli Wetan, Kecamatan Tapen, Kabupaten Bondowoso - Elzha Putri Widya Yurisa (Faculty of Law, University of Jember, Indonesia, 2022)
Bondowoso Regency Land Office is carrying out Complete Systematic Registration (PTSL) activities with 12 (Twelve) villages in Bondowoso Regency, one of which is in Mangli Wetan Village, Tapen District with the target of Land Rights Certificates (SHAT) and PBT (Map of Fields). Land) in the amount of 1600 (One Thousand and Six Hundred) plots of land which must be completed in 2022 (Two Thousand Twenty Two). Mangli Wetan Village is one example that indigenous peoples still maintain customary land law in Mangli Wetan Village with a large amount of uncertified land and land that has been transferred before the Village Head and crossed out in the Village registration book (Letter C). The research method used is socio-legal, by conducting research directly in society, to find out and understand the legal problems that occur and to deal with applicable laws and regulations. This study aims to determine the government's strategic program carried out by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency through Complete Systematic Land Registration (PTSL), especially for lands recorded in the Village Registration Book (Letter C) whose rights have not been certified in Mangli Village. Wetan, Tapen District, Bondowoso Regency. The research method used is socio-legal, by conducting research directly in the community, to find out and understand the legal problems that occur and are faced with applicable laws and regulations. The belief in the existence of customary law that arises has become the foundation and stronghold for indigenous peoples to prevent disputes for the people in Mangli Wetan Village. Therefore, appreciation is needed for indigenous peoples in Mangli Wetan Village, Tapen District, Bondowoso Regency. KEYWORDS: Legal Certainly, Adat’s Society, PTSL Program.